Difference in kick motion of adolescent soccer players in presence and absence of low back pain - Tojima, M.; Torii, S. (Gait and Posture, 2018)
Many adolescent soccer players experience low back pain (LBP). However, there are no reports studying the kick motion of adolescent soccer players experiencing LBP. This study aimed to clarify the kick motion of adolescent soccer players in the presence and absence of LBP. We recruited 42 adolescent soccer players and divided them into two groups according to the presence of LBP (LBP group, n=22) and absence of LBP (NBP group, n=20). We measured real-time kick motion using a three-dimensional motion analysis system. We placed 65 spherical markers on each anatomical landmark and calculated the angle of the lumbar spine, center of mass (COM) of the whole body, and displacement of the support foot. We used an unpaired t-test to compare the data between the groups. Compared with the NBP group, the LBP group showed a lateral shift in COM, which increased the duration of kick motion. The presence of LBP affected the posterior positioning of the support foot and restricted the player`s lumbar spine from bending laterally. A lateral shift in COM and larger rotation of the lumbar spine could stress the lumbar spine during kick motion. Therefore, coaches and athletic trainers should pay attention to soccer players` lumbar spine rotation and the COM shift during kick motion. This would be important for preventing LBP in adolescent soccer players.